Determination of the Number of Flights and Passengers, Promotion and Marketing, and Retail Availability of Aero and Non-Aero Targets at Raja Haji Fisabilillah Tanjung Pinang Airport - Brahmantyo, Agung; Simarmata, Juliater (Dinasti Publisher, 2024)
The article on determining the number of flights and passengers, promotion and marketing and retail availability of aero and non-aero targets at Raja Haji Fisabilillah Tanjung Pinang Airport is a scientific literature review article within the scope of marketing management science. This article aims to create a hypothesis regarding the relationship between factors, which can then be used for further research in the field of human resource management. Descriptive qualitative research methodology was used in this research. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The findings of this research are as follows: 1) The number of flights and passengers influences the aero and non-aero targets at Raja Haji Fisabilillah Tanjung Pinang Airport; 2) Promotion and Marketing influence aero and non-aero targets at Raja Haji Fisabilillah Tanjung Pinang Airport; and 3) Retail availability influences aero and non-aero targets at Raja Haji Fisabilillah Tanjung Pinang Airport.